Analysis of the Effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on Stock Prices of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2023-2024 Period - Yekti, Yekti Nilasari; Asmu'i, Faishal; Indonesia, Indonesia (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
This study aims to examine the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on stock prices of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period. This research employs a quantitative approach, with a population of 228 companies and a purposive sampling method resulting in 137 selected companies. The data were analyzed using multiple linear regression with t-tests and F-tests to test the hypotheses. The partial test results (t-test) show that ROA has a significant effect on stock prices, with a calculated t-value of 1.486, which is greater than the t-table value of 0.67749, and a significance level of 0.000 < 0.05. This indicates that a company's profitability plays an important role in driving stock price increases. DER also has a significant partial effect on stock prices, with a t-value of 0.692 > 0.67749 and a significance level of 0.004 < 0.05, suggesting that a company’s capital structure is also a key consideration for investors in valuing stocks. Furthermore, the simultaneous test (F-test) shows that ROA and DER together significantly influence stock prices, with an F-value of 7.554, which exceeds the F-table value of 3.3541, and a significance level of 0.002 < 0.05. These findings indicate that the combination of profitability and leverage meaningfully affects investor valuation and plays a vital role in stock investment decision-making